O status da nasal palatal [ɲ] em João Pessoa - Pedrosa, Larissa Moraes (2016)
The main purpose of this academic work is to demonstrate the dynamic and social aspect of language, according as that speakers uses various forms of the nasal consonant palatal segment, the /ɲ/, depending on the linguistic and extralinguistic factors that they are submitted. The specific purposes are: identify the linguistic and extralinguistic conditions that may influence the variation of the nasal palatal /ɲ/; observe the variable accomplishment of the palatal nasal consonant as a variable null [ø] or the maintenance of the phoneme [ɲ], and reveal if the palatal nasal undergoes a process of a stable variation or language change process. This research corpus was taken from VALPB Project (HORA; PEDROSA, 2001), that has 34 informants, so we could verify is the speakers of Portuguese in a community of João Pessoa vary or not the palatal nasal. For this, we verified the variables tonicity word, following phonological context, precedent phonological context, number of syllables, grammatical category and sex as the most relevant for the deletion of palatal nasal in words. Our results shows that when the words has the palatal nasal consonant as a variable null, in the process of variation, the nasality of /ɲ/ remains, standing in the preceding vowel. Besides that, we verified the relevance of precedent phonological context, especially when it was the phoneme [i], because when the palatal nasal is deleted, the [i] keeps the distinctive feature coronal of [ɲ]. Our phenomenon is in a stable variation, given that the same speaker uses both a term with the maintenance of sound, as used with the deletion, at different times.